Sistem Pakar Narcolepsy dengan Metode Forward Chaining - Suci Wahyuni (Universitas Putra Indonesia YPTK Padang, 2019)
Narcolepsy is a disease that causes victims to often get drowsy attacks, like other sleep disorders he is rarely recognized by the public. Narcolepsy is also a sleep attack where the sufferer is very difficult to maintain a conscious state. Drowsiness can disappear if you have slept within 15 minutes, but drowsiness will come back next, and at night narcolepsy can not sleep. The habit is also an obstacle that is often found in adolescents or even adults lately, one of the negat ive effects of sleepiness is the constraint of our work. Many of us are not aware of the disease caused by narcolepsis, so that habit triggers a bad impact on the body. Following this up, a system was created that was able to provide information like a doctor to patients against narcolepsis using the forward chaining method. With the aim of the system can provide information on the impact faced by narcolepsis. This system was built using research and development methods which point to the output in the form of expert system applications with the reading of the data carried out by forward chaining